The Effects of Verbal Encouragement and Compliments on Physical Performance and Psychophysiological Responses During the Repeated Change of Direction Sprint Test - Sahli, Hajer; Haddad, Monoem; Jebabli, Nidhal; Sahli, Faten; Ouergui, Ibrahim; Ouerghi, Nejmeddine; Bragazzi, Nicola Luigi; Zghibi, Makrem (Frontiers in Psychology, 2022)
The general and sports psychology research is limited regarding the difference between the effects of verbal encouragement (VE) or compliment methods during high-intensity functional exercise testing. The purpose of this study was to explore the effects of VE and compliments on the performance of the repeated change-of-direction (RCOD) sprint test. A total of 36 male students in secondary school participated voluntarily in the study. They were divided equally into three homogeneous groups [VE group, compliment group (CG), and control group) and performed a standardized one repetition RCOD. The RCOD (6 × 20 m with 25-s active recovery) test consisted of a 100°change in the direction at every 4 m. Outcomes included performance indices (fast time, average time, and total time), rating of perceived exertion (RPE), and feeling scale scores. VE and the compliment increased the performance indices and RPE compared with the control group. In conclusion, VE during the exercise testing would be more beneficial for optimal performance and RPE compared with the compliment and control groups. However, the moods, during RCOD, reproduce more positively during compliment conditions than the VE and control groups.